Molybdenum supply increases 15N-nitrate uptake by maize - Moreira, Lílian A.; Tränkner, Merle; Mariano, Eduardo; Otto, Rafael (Frontiers in Plant Science, 2025)
Nitrogen (N) is widely used in maize (Zea mays L.) production. The supply of molybdenum (Mo) can increase the recovery of N by the plant due to the role of this micronutrient in the assimilation of nitrate through nitrate reductase (NR). We aimed to evaluate N metabolism and auxiliary measurements in maize as affected by combined N and Mo omission or supply under controlled conditions. Plants were grown for 28 d in a nutrient solution without Mo and N, with Mo and N, and under the omission of Mo or N. The treatments with omission received nutrients with foliar application or via nutrient solution after 28 d. Gas exchange, chlorophyll and anthocyanins indexes, and N accumulation were evaluated at 28, 35, and 44 d after transplanting (DAT). The amino acid profile was altered due to Mo and N supply to the plants, as well as the uptake and accumulation of nitrate. The highest biomass production was quantified in the positive control, supplied by the nutrient solution and later by the absence of Mo, being the foliar application inferior to this treatment. Maize biomass, with the omission of N and Mo, was 31 % lower than the supply of both nutrients. Molybdenum favors nitrate uptake by maize, mainly when supplied through the nutrient solution.